2020
DOI: 10.7759/cureus.7198
|View full text |Cite
|
Sign up to set email alerts
|

How and Why Paediatric Weight Estimation Systems Fail - A Body Composition Study

Abstract: Background Weight estimation during medical emergencies in children is essential, but fraught with errors if the wrong techniques are used, which may result in critical drug dosing errors. Individualised weight estimation is required to allow for accurate dosing in underweight and obese children in particular. This study was designed to evaluate the associations between weight estimations from different systems and body composition in order to establish how and why they may perform well or poorly. Methods A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
3
10
0
2
Order By: Relevance
“…Similarly, Wells et al found that none of the age-based formulas could predict the actual body weight with reasonable accuracy, especially in obese subjects. 18 , 19 Our data reinforce the ERC guidelines that discourage using age-based formulas in paediatric clinical settings.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, Wells et al found that none of the age-based formulas could predict the actual body weight with reasonable accuracy, especially in obese subjects. 18 , 19 Our data reinforce the ERC guidelines that discourage using age-based formulas in paediatric clinical settings.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, either over- or under-weight approximation can lead to suboptimal medication dosage and related morbidity and mortality. 10 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to accuracy, usability is also important in a weight estimation system – it must not require a substantial amount of training to learn, and must be quick and easy to use, as weight estimation itself can lead to delays in emergency treatment [44]. The PAWPER XL and PAWPER XL-MAC systems were designed for emergency use, and data from paediatric studies suggested that they fulfil the accuracy and usability criteria and are relatively less impacted by human factor errors than other weight estimation systems [27, 47, 48]. This needs to be established in prospective studies of emergency care in adult patients, however.…”
Section: Discussionmentioning
confidence: 99%
“…The Broselow method was developed in the 1980s and has been modified and studied fairly extensively in the intervening years, with varying results. 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The Handtevy system, initially developed in 2010 as a length and age-based system, has been adapted and can now be used as an exclusively age-based tool for weight estimation. 21 There are few studies evaluating the Handtevy system, most of which were published prior to the development of the solely age-based application, however Rappaport, et al recently published a manuscript reporting almost 90% dosing accuracy using the Handtevy Field Guide (accuracy was based on correct use of the field guide/patient age, not patient weight).…”
Section: Introductionmentioning
confidence: 99%